DETEKSI DINI POTENSI KEBANGKRUTAN PT. ANGKASA PURA I (PERSERO) DENGAN METODE SPRINGATE DAN ZMIJEWSKI - Arief Nurdiannova Qurochman (Sekolah Tinggi Ilmu Ekonomi Yapan, 2017)
An initial detection toward bankruptcy is needed by a company to be aware of such condition. By using that detection, management can rule the enterprise running according to the policy of the company. The early detection of bankruptcy in this research used Springate score and Zmijewski score. The sample used in this observation is some data taken from balance sheet and financial statement of PT. Angka Pura I (Persero) from year of 2012 to 2016. The observation method is qualitative, that is by inserting some related data into the formula of Springate score and Zmijewski score.Based on the counting of the Springate score, PT. Angkasa Pura is indicated to get bankruptcy which is shown by scores of below 0,862 from year of 2012 to 2016. Whereas, according to the Zmijewski score, the company is valued healthy, because their scores from 2012 to 2016 are still negative, but from year to year the scores are getting closer to zero or positive. So, it has to be noticed to prevent from getting worse (getting positive score).